Triglyceride-glucose index and related parameters in the diagnosis and predictive efficacy for older adults with NAFLD/MASLD: a prospective cohort study - Chen, Yuwei; Lin, Xinjun; Chen, Yanqiu; Wang, Bingcai; Xu, Chaoxiang; Wang, Yaoguo (Frontiers in Medicine, 2025)
BackgroundNon-alcoholic fatty liver disease (NAFLD) affects over 25% of the global population and is associated with numerous comorbidities. Several indices, including the triglyceride-glucose (TyG) index, TyG-waist circumference (TyG-WC), TyG-body mass index (TyG-BMI), and TyG-waist-height ratio (TyG-WHtR), have been strongly associated with NAFLD. However, research on the stratification of hepatic steatosis severity in NAFLD, particularly in older adults, remains limited. This study aimed to investigate the relationship between TyG index and NAFLD in elderly individuals.MethodsThis study analyzed physical examination data from 3,954 individuals aged 60 years or older, collected during a 2-year follow-up period at Nan’an General Hospital, Nanqiao Branch. Binary logistic regression and receiver operating characteristic curve analyses were employed to examine the relationship between the TyG index and NAFLD and its various pathological stages. Additionally, the change in the TyG index during follow-up was calculated to assess its predictive significance for NAFLD progression.ResultsThe TyG, TyG-WC, TyG-BMI, and TyG-WHtR quartiles were grouped for analysis in patients with NAFLD, revealing significant differences in hepatic steatosis severity between the groups (p < 0.001). All four parameters were significant predictors of hepatic steatosis severity (p < 0.001). After further adjusting for age, sex, marital status, alcohol consumption, smoking status, exercise, hypertension, diabetes, coronary heart disease, uric acid, HDL, ALT, and AST, the odds ratios (ORs) for the fourth quartile were 4.36 (3.39–5.61), 19.77 (14.92–26.22), 28.23 (20.81–28.28), and 14.56 (11.05–19.19), with all p values <0.001. The areas under the curve values for the four parameters for predicting NAFLD status were 0.744, 0.811, 0.840, and 0.813, respectively. Furthermore, an increase in the TyG index was identified as a risk factor for disease progression, while a decrease was associated with improvement in NAFLD severity.ConclusionThe TyG index and its related parameters serve as reliable, non-invasive indicators for the diagnosis and progression of NAFLD in elderly populations. Monitoring changes in these indices can improve early detection and management of NAFLD.